Association between weight-adjusted waist index and testosterone deficiency in adult American men: findings from the national health and nutrition examination survey 2013-2016 - Dalu Liu; Yuanyuan Li; Nuo Ji; Wei Xia; Bo Zhang; Xingliang Feng (BMC, 2024)
Abstract Background Testosterone deficiency (TD) and obesity are globally recognized health concerns, with a bidirectional causal relationship between them. And a newly discovered obesity indicator, the Weight-Adjusted-Waist Index (WWI), has been proposed, demonstrating superior adiposity identification capability compared to traditional body mass index (BMI) and waist circumference (WC) indicators. Therefore, we present the inaugural investigation into the associations of WWI with total testosterone levels and the risk of TD. Methods Data restricted to the National Health and Nutrition Examination Survey (NHANES) between 2013 and 2016 were analyzed. Only males aged > 20 years who completed body measures and underwent serum sex hormone testing were potentially eligible for analysis. Weighted multivariable linear regression and logistic regression analyses were employed to investigate the relationships between WWI and total testosterone levels, and the risk of TD, respectively. Smooth curve fittings and weighted generalized additive model (GAM) regression were conducted to examine the linear relationship among them. Additionally, subgroup analyses with interaction tests were performed to assess the stability of the results. Results Finally, a total of 4099 participants with complete data on testosterone and WWI were included in the formal analysis. The mean age of study participants was 46.74 ± 0.35 years with a TD prevalence of 25.54%. After adjusting all potential confounders, the continuous WWI displayed a negative linear relationship with total testosterone levels (β=-61.41, 95%CI: -72.53, -50.29, P < 0.0001) and a positive linear relationship with risk of TD (OR = 1.88, 95%CI: 1.47, 2.39, P < 0.0001). When WWI was transformed into quartiles as a categorical variable, participants in Q4 exhibited lower total testosterone levels (β=-115.4, 95%CI: -142.34, -88.45, P < 0.0001) and a higher risk of TD (OR = 3.38, 95% CI: 2.10, 5.44, P < 0.001). These associations remained stable in subgroup analyses without significant interaction (all P for interaction > 0.05). Conclusions This investigation firstly unveiled a negative linear association between WWI and total testosterone levels, coupled with a positive linear relationship with the prevalence of TD in U.S. male adults aged 20 years and older. Further studies are needed to validate the potential utility of WWI for the early identification and timely intervention of TD.